The right to education and study and women's labor rights in Iranian jurisprudence and law and the UNESCO 2030 document - Ali Bakhshzadeh, OmolBanin (2021)
In this article, the researcher seeks to examine the right to education and study and women's labor rights in Iranian jurisprudence and law and the 2030 UNESCO document. The present study is a descriptive-analytical study using the library method to investigate the question. The results of the study indicate that both in Islam and Iranian law, as well as in international documents, the equality of women's rights with men is emphasized but the concept of equality in Islam is explained in the sense of proportion and not equality in international instruments, however, equality between men and women means that their rights are equal. Regarding the right to education, there is no contradiction between Iranian jurisprudence and law and the 2030 document because in both Iranian jurisprudence and law, as well as in the documents emphasized in the 2030 document, which leads to the empowerment of women, the right to equal education has been emphasized. Regarding labor rights, it should be said that in the conventions of the International Labor Organization, which are among the documents considered in the 2030 document in the field of women's empowerment, concessions in the field of women's labor rights have been included for them. Prohibition of hazardous work, breastfeeding hours, maternity leave are among these rights. In Iranian labor law, these advantages are also considered for women, and therefore it seems that Iranian labor law is in accordance with international instruments. The issue of equality can be analyzed in such a way that, although there are biological and natural differences between men and women, this situation should not lead to legal differences. Basically, biological differences are concerned with the realities of human existence, and the legal debate is concerned with human needs and although individuals are different in existential realities, they can also be similar in legal requirements.